Strongly Interacting Isotopic Bose-Fermi Mixture Immersed in a Fermi Sea - Wu, C; Santiago, I; Park, J; Ahmadi, P; Zwierlein, M (2011)
We have created a triply quantum degenerate mixture of bosonic $^{41}$K and two fermionic species $^{40}$K and $^6$Li. The boson is shown to be an efficient coolant for the two fermions, spurring hopes for the observation of fermionic superfluids with imbalanced masses. We observe multiple heteronuclear Feshbach resonances, in particular a wide s-wave resonance for the combination $^{41}$K-$^{40}$K, opening up studies of strongly interacting {\it isotopic} Bose-Fermi mixtures. For large imbalance, we enter the polaronic regime of dressed impurities immersed in a bosonic or fermionic bath.